Evaluasi Pembelajaran Berbasis Outcomes di Pendidikan Tinggi Islam: Suatu Kajian Konseptual - Endang, Ujang; Husni, Husni; Sahal, Yosep Farhan Dafik (Jurnal Penelitian Pendidikan Islam, 2020)
This article attempts to explore the concept of outcomes-based evaluation and then offers it as one of the evaluation models in Islamic higher education. By using the literature review method, this study successfully traced the outcomes-based evaluation concept, which is thought to be more suitable for use in Islamic higher education institutions. One of the characteristics of learning outcomes in Islamic higher education institutions is the use of abstract terms such as understanding, understanding, living, believing, realizing, and believing. These terms are often used when lecturers conduct assessments and evaluations on several variables that are not easily measured, such as religiosity, faith, morals, character, personality, and integrity. Statistically, these variables can still be measured, but the measurement instruments used must meet two conditions, namely valid and reliable. However, the current higher education system demands a measurable evaluation system, so that even though outcomes-based learning evaluation models become quite troublesome, Islamic higher education is still required to introduce and use them.